Measuring Visual Function Using the MultiQuity System: Comparison with an Established Device. (16th December 2014) - Smolarek-Kasprzak, Patrycja; Nolan, John M.; Beatty, Stephen; Dennison, Jessica; Akuffo, Kwadwo Owusu; Kuchling, Robert; Stack, Jim; O'Regan, Graham
Abstract : Purpose . To compare measures of visual acuity (VA) and contrast sensitivity (CS) from the Thompson Xpert 2000 and MultiQuity (MiQ) devices. Methods . Corrected distance VA (CDVA) and CS were measured in the right eye of 73 subjects, on an established system (Thompson Xpert) and a novel system (MiQ 720). Regression was used to convert MiQ scores into the Thompson scale. Agreement between the converted MiQ and Thompson scores was investigated using standard agreement indices. Test-retest variability for both devices was also investigated, for a separate sample of 24 subjects. Results . For CDVA, agreement was strong between the MiQ and Thomson devices (accuracy = 0.993, precision = 0.889, CCC = 0.883). For CS, agreement was also strong (accuracy = 0.996, precision = 0.911, CCC = 0.907). Agreement was unaffected by demographic variables or by presence/absence of ocular pathology. Test-retest agreement indices for both devices were excellent: in the range 0.88–0.96 for CDVA and in the range 0.90–0.98 for CS. Conclusion . MiQ measurements exhibit strong agreement with corresponding Thomson measurements, and test-retest results are good for both devices. Agreement between the two devices is unaffected by age or ocular pathology.